2013
DOI: 10.4314/ajtcam.v10i5.4
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of aqueous leaf extract of <i>Aspilia Africana</i> C.D. adams on some haematological parameters in rats

Abstract: Several medicinal plants have been documented for their haematological effects either at low or high concentration but very little is known about Aspilia africana. The aim of the study was to investigate the acute effects of aqueous leaf extract of Aspilia africana at different concentrations on some haematological parameters in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
(10 reference statements)
0
17
0
1
Order By: Relevance
“…This is consistent with the finding of an earlier study in which Aspilia africana aqueous extract stimulated white blood cell proliferation. 34 The rise in white blood cell count in the present investigation may not necessarily be attributed to the presence of infection but may have been triggered by the method of blood collection or by stress factors induced by oral intake of the extracts. 35,36 The effects of the aqueous extract on renal parameters when compared to the chloroform extract suggest that the components in Aspilia africana that influenced kidney function are likely polar in nature.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…This is consistent with the finding of an earlier study in which Aspilia africana aqueous extract stimulated white blood cell proliferation. 34 The rise in white blood cell count in the present investigation may not necessarily be attributed to the presence of infection but may have been triggered by the method of blood collection or by stress factors induced by oral intake of the extracts. 35,36 The effects of the aqueous extract on renal parameters when compared to the chloroform extract suggest that the components in Aspilia africana that influenced kidney function are likely polar in nature.…”
Section: Resultsmentioning
confidence: 60%
“…33 In contrast, it has previously been reported that at higher doses (250 -500 mg/kg body weight), the aqueous extract of Aspilia africana stimulated erythropoiesis. 34 Mean corpuscular volume was not significantly different (p>0.05) among the groups, an indication that the plant did not induce significant alterations in blood cell volume. In addition, packed cell volume of blood was not significantly different (p>0.05) ( Table 2).…”
Section: Resultsmentioning
confidence: 88%
“…35 Significant lowering of WBC counts found after treatment with the medicines could be due to their toxic effects. This also suggests their potential to affect the immune system adversely by reducing the ability to decrease inflammation, fight off invading infections and diseases, 35 , 36 especially if taken over a prolonged period. Decreases in the hematological parameters by KT and KBA also suggest that intake of these medicines may result in anemia.…”
Section: Discussionmentioning
confidence: 99%
“…Decreases in the hematological parameters by KT and KBA also suggest that intake of these medicines may result in anemia. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Indomethacin was dissolved in 5% sodium bicarbonate solution (Na2HCO3) to create a clear solution. The dose of Indo was selected from published literature according to Ajeigbe et al, (2014). Indomethacin (Liometacen) is the most favored drug to generate an experimental ulcer model because its potential to make ulcer is higher than other NSAIDs.…”
Section: Experimental Designmentioning
confidence: 99%